Spanish Version of the Teachers’ Sense of Efficacy Scale: An Adaptation and Validation Study - Fátima Salas-Rodríguez (Frontiers Media S.A., 2021)
The Teachers’ Sense of Efficacy Scale (TSES) has been the most widely used instrument to assess teacher efficacy beliefs. However, no study has been carried out concerning the TSES psychometric properties with teachers in Mexico, the country with the highest number of Spanish-speakers worldwide. The purpose of the present study is to examine the reliability, internal and external validity evidence of the TSES (short form) adapted into Spanish with a sample of 190 primary and secondary Mexican teachers from 25 private schools. Results of construct analysis confirm the three-factor-correlated structure of the original scale. Criterion validity evidence was established between self-efficacy and job satisfaction. Differences in self-efficacy were related to teachers’ gender, years of experience and grade level taught. Some limitations are discussed, and future research directions are recommended.